Find (f∘g)(x).

f(x)=x+4
g(x)=x2+5x
Write your answer as a polynomial in simplest form.
(f∘g)(x)=

1 answer

(f∘g)(x) would be equal to f(g(x)). Therefore, we need to substitute g(x) into f(x).

f(g(x)) = f(x^2 + 5x)

Now substitute x^2 + 5x into f(x):

f(x^2 + 5x) = (x^2 + 5x) + 4

Simplifying, the final polynomial form is:

(f∘g)(x) = x^2 + 5x + 4
Similar Questions
    1. answers icon 20 answers
  1. 1. Divide. Write your answer in simplest form.2/3 / 1/4 2. Find the product. 1/2 x 3/7 3. Divide. Write the quotient in simplest
    1. answers icon 18 answers
  2. a)Find a Cartesian equation relating and corresponding to the parametric equations: x=2sin(3t), y=9cos(3t). Write your answer in
    1. answers icon 2 answers
  3. Find the product. Your answer should be in simplest form.1. one-third• 7 (1 point) one over twenty-one two and one-seventh two
    1. answers icon 72 answers
more similar questions